Teaching competencies of college instructors of calayan educational foundation, inc : an assessment - Go, Filemon Jimenez (Manila : National University, 2007)
The result of the study will reveal the teaching competencies of college instructors of CEFI in terms of Personal and Professional Qualities, Mastery of Subject Matter, Instructional Competence, Communication Skills, Classroom Management, and Guidance Skills. The study may also identify some problems encountered by respondents which need to be re-examined and improved.
Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- Abstract -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.